CARIES IN SCHOOL CHILDREN AND TREATMENT PREVENTIVE MEASURES (American Journal of Pedagogical and Educational Research, 2023)
The prevalence and intensity of dental caries in children has decreased in many countries of the world over the past 20-30 years [1], and this phenomenon in the late XX and early XXI centuries coincided with the widespread introduction of systemic fluoridation programs.